Development of non-fluorine superhydrophobic textiles using polypropylene resins. Issue 19 (October 2019) - Kim, Jung Yoon; Yun, Changsang; Park, Chung Hee
This study aims to develop environment-friendly superhydrophobic textiles forming nanoparticles of polypropylene that have intrinsically low surface energy, and thus achieving the requirements for superhydrophobicity, such as hierarchical roughness and low surface energy at once. This work mainly studies the influences of tacticity (isotactic, atactic), concentration (10, 20, 30 and 40 mg/ml), drying temperature (30℃ and 70℃) and the mixing ratio of the solvent/non-solvent (9:1, 8:2, 7:3 and 6:4) on the coating morphology and wettability. In the case of isotactic polypropylene, the optimal condition showing the water contact angle of 173° and the water shedding angle of 4° was at 70℃ drying temperature, 30 mg/ml concentration and 6:4 solvent/non-solvent mixing ratio. Amorphous polypropylene showed the water contact angle of 163° and the water shedding angle of 9° at the condition of 30℃ drying temperature, 40 mg/ml concentration and 8:2 solvent/non-solvent mixing ratio. It was revealed that superhydrophobicity by amorphous polypropylene was exhibited at lower drying temperature and lower mixing ratio for the non-solvent. This is attributed to the different evaporation temperature or speed of the solvent/non-solvent mixing according to the tacticity of polypropylene. This study demonstrated that environmental-friendliness was improved in that superhydrophobic textiles were developed without fluorine compounds, maintaining vapor permeability. This study also developed a finishing method using amorphous polypropylene under a mild condition in terms of drying temperature and solvent toxicity, which is expected to be applicable not only to polyester but also to various fabrics.